Commentary on "The Promise of the Foreign" - Barbaza, Remmon E (Archīum Ateneo, 2011)
Guided by key Heideggerian insights, this review focuses on two points: 1) the relationship between what is foreign and what is one’s own; 2) language and history. The promise of the foreign belongs to the allure of the unknown, and the impulse to know the unknown belongs to the “de-distancing” character of the human—the tendency of human beings to bring things to nearness, thereby negating the distance that stands between them and the things they encounter in the world. Rafael has shown that the Filipinos were driven by the desire to bring what is foreign (in their case, Spain) near to them (e.g., by way of assimilation) in order to own and be owned by what otherwise remains distant and alien. But along with the promise of the foreign comes the risk of betrayal. The betrayal of the promise is ultimately the result of the mistaken fundamental assumption that one can get around language and history. The important and fascinating work of Rafael serves as a warning against an even more tragic betrayal: the betrayal of one’s own history, which includes not the just the past and the present, but even more that which is yet to come.